Assessing management plans for the recovery of the european eel ( Anguilla anguilla ): a need for multi-objective analyses - Bevacqua, Danièle; Melià, Paco; Crivelli, Alain Jean; Gatto, Marino; de Leo, Giulio Alessandro (HAL CCSD, 2007)
International audience